2005
DOI: 10.1128/mcb.25.4.1475-1488.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Smad7 and β-Catenin: Importance for Transforming Growth Factor β-Induced Apoptosis

Abstract: Members of the transforming growth factor ␤ (TGF-␤) and Wnt/wingless superfamilies regulate cell fate during development and tissue maintenance. Here we report that Smad7 interacts with ␤-catenin and lymphoid enhancer binding factor 1/T-cell-specific factor (LEF1/TCF), transcriptional regulators in Wnt signaling, in a TGF-␤-dependent manner. Smad7 was found to be required for TGF-␤1-induced accumulation of ␤-catenin and LEF1 in human prostate cancer (PC-3U) cells as well as in human keratinocytes (HaCaT cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 62 publications
7
112
0
Order By: Relevance
“…A cross-talk between TGF-β and Wnt signaling pathways through physical association of β-catenin and Smad7 has been reported (Edlund et al, 2005). This cross-talk was found to be important for TGF-β-induced apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…A cross-talk between TGF-β and Wnt signaling pathways through physical association of β-catenin and Smad7 has been reported (Edlund et al, 2005). This cross-talk was found to be important for TGF-β-induced apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…However, a proapoptotic role of HGF (Arakaki et al, 1998;Matteucci et al, 2003;Rasola et al, 2004) and b-catenin (Kim et al, 2000;van Gijn et al, 2001;Edlund et al, 2005) was also reported in several models. Here, we show that the HGFR transduction axis and the b-catenin/TCF pathway cooperate in underpinning survival signals, whose importance probably increases during carcinoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, these complexes inhibit phosphorylation of ␤-catenin and thereby its degradation (62). Furthermore, SMAD 7 interacts with ␤-catenin to modulate TGF-␤ induced apoptosis, as SMAD7 acts as positive regulator of the TGF-␤-activated pathway involving TAK1-MKK3 and p38 mitogen-activated kinases, leading to induction of c-Myc and p53 and subsequently apoptosis (46,(62)(63)(64). Indeed, increased apoptosis was detected by PARP1 cleavage, despite of the proliferative phenotype.…”
Section: Discussionmentioning
confidence: 99%